2017
DOI: 10.1128/aem.03467-16
|View full text |Cite
|
Sign up to set email alerts
|

Critical Concentration of Lecithin Enhances the Antimicrobial Activity of Eugenol against Escherichia coli

Abstract: Lecithin is a natural emulsifier used in a wide range of food and nonfood applications to improve physical stability, with no known bioactive effects. In this study, the effect of lecithin on the antimicrobial performance of a constant eugenol concentration was tested against three Escherichia coli strains (C600, 0.1229, and O157:H7 strain ATCC 700728). This is the first study, to our knowledge, focusing on lecithin at concentrations below those commonly used in foods to improve the stability of oil in water e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…When the critical synergistic concentrations were above the CMC, the enhanced antimicrobial property of eugenol may have been due to the encapsulation of eugenol into phospholipid micelles. However, with concentrations below the CMC, the phospholipid may form phospholipid-rich "patches" on the eugenol droplets as discussed in our previous study (11). The partition of phospholipids into the E. coli cell membrane (and therefore the modification of the membrane fluidity and permeability for hydrophilic compounds) is another mechanism that we plan to investigate (32).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…When the critical synergistic concentrations were above the CMC, the enhanced antimicrobial property of eugenol may have been due to the encapsulation of eugenol into phospholipid micelles. However, with concentrations below the CMC, the phospholipid may form phospholipid-rich "patches" on the eugenol droplets as discussed in our previous study (11). The partition of phospholipids into the E. coli cell membrane (and therefore the modification of the membrane fluidity and permeability for hydrophilic compounds) is another mechanism that we plan to investigate (32).…”
Section: Discussionmentioning
confidence: 88%
“…However, previous reports showed that the antimicrobial properties of EO against E. coli were not enhanced when EOs were combined with lecithin (8,9) or observed that waterinsoluble surfactants (including lecithin) in nanoemulsions diminished the antimicrobial efficacy of EOs (10). In contrast, we previously reported that the antimicrobial properties of eugenol were significantly improved when lecithin was added at a critical low concentration (11). Nanoscale (Ͻ50-nm) aggregates were observed when eugenol was mixed with critical synergistic concentration of lecithin, and it was suggested that electrostatic interactions between charged phospholipids and the negatively charged bacterial cell membrane were responsible for the improved antimicrobial properties.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…Emulsifiers promote fatty acids' incorporation into micelles and increase the digestibility of dietary lipids in the duodenum of chickens (13,14) . De-oiled soyabean lecithin (DSL) is a mixture of amphiphilic phospholipids, which has good emulsification property (15) .…”
mentioning
confidence: 99%